Pender’s Health Promotion Modeland Application for The Pandemic of Coronavirus 2019 Preventing in the Elders - Chomphunit, Paphadar; Saengploy, Thitiporn; Fhunpayom, Sillapachai (NU Journal of Nursing and Health Sciences, 2020)
In December 2019 , World Health Organization (WHO) was received oftheCoronavirus Situation, which causes of the disease and has spread to other countries. In Thailand, the total number of cases reported is currently more than 4,000 cases and 60 death (Department of Disease Control, 2020). The study found that those who were sick and died most of them are elderly. Especially the elderly with congenital disease. Pender’s health promotion model is a theoretical concept used in health promotion, intended to increase the level of a person’s well-being.The 6 main components are: 1) Health responsibility 2) physical activity 3) nutrition 4) interpersonal relations 5) spiritual growthand 6) stress management. This will be very useful for the elderly that can apply this idea to change the behavior to prevent coronavirus disease 2019.